THE INFLUENCE OF MONEY ATTITUDE ON FINANCIAL WELL-BEING ON MARRIED WORKERS - Alif Naafi Ardradhika; Alvira Roslia; Ananda Putri (Universitas Gunadarma, 2023)
The Covid-19 pandemic has caused several changes in various sectors of life. The most noticeable change is in economic conditions. In the current post-pandemic situations, people have also changed their perception about the concept of financial well-being. According to several studies, financial well-being is influenced by several factors, one of them is money attitude. The purpose of this study is to determine the influence of money attitude on financial well-being on married workers. The sample of this study were 70 married workers in the Greater Jakarta area. Sampling using nonprobability sampling technique with purposive sampling method. This study uses the Money Attitude Scale and the Financial Well Being Scale as data collection tools. Based on the simultaneous data analysis, a significance value of .000 (p-value < .05) was obtained, which means that all of the money attitude dimensions were influential on financial well-being. Based on the partial data analysis, the dimensions of retention-time and distrust were significantly influenced, while the dimensions of power-prestige and anxiety were insignificantly influenced. Additionally, there was a financial well-being difference based on income and occupation.